cAMP activates the generation of reactive oxygen species and inhibits the secretion of IL-6 in peripheral blood mononuclear cells from type 2 diabetic patients - Isoni, Camila Armond (Landes Bioscience, 2009)
Peripheral blood mononuclear cells (PBMNC) from patients with type 2 diabetes (DM2) have generated higher levels of reactive oxygen species (ROS) that were higher than those in cells from healthy individuals. In the presence of a cAMP-elevating agent, ROS production was significantly activated in PBMNC from DM2 patients but it was inhibited in cells from healthy subjects. Higher levels of IL-6 has been detected in the supernatant of PBMNC cultures from DM2 patients in comparison with healthy controls. When cells were cultured in the presence of a cAMP-elevating agent, the level of IL-6 decreased has by 46% in the supernatant of PBMNC from DM2 patients but it remained unaltered in controls. No correlations between ROS and IL-6 levels in PBMNC from DM2 patients or controls have been observed. Secretions of IL-4 or IFN by PBMNC from patients or controls have not been affected by the elevation of cAMP. cAMP elevating agents have activated the production of harmful reactive oxidant down modulated IL-6 secretion by these cells from DM2 patients, suggesting an alteration in the metabolic response possibly due to hyperglicemia. The results suggest that cAMP may play an important role in the pathogenesis of diabetes.